Β-Cleavage of the prion protein in the human eye: Implications for the spread of infectious prions and human ocular disorders. (November 2021) - Chaudhary, Suman; Ashok, Ajay; Wise, Aaron S.; Rana, Neil A.; Kritikos, Alexander E.; Lindner, Ewald; Singh, Neena
Abstract: Recently, we reported β-cleavage of the prion protein (PrP C ) in human ocular tissues. Here, we explored whether this is unique to the human eye, and its functional implications. A comparison of the cleavage pattern of PrP C in human ocular tissues with common nocturnal and diurnal animals revealed mainly β-cleavage in humans, and mostly full-length PrP C in animal retinas. Soluble FL PrP C and N-terminal fragment (N2) released from β-cleavage was observed in the aqueous and vitreous humor (AH & VH). Expression of human PrP C in ARPE-19 cells, a human retinal pigmented epithelial cell line, also showed β-cleaved PrP C . Surprisingly, β-cleavage was not altered by a variety of insults, including oxidative stress, suggesting a unique role of this cleavage in the human eye. It is likely that β-cleaved C- or N-terminal fragments of PrP C protect from various insults unique to the human eye. On the contrary, β-cleaved C-terminus of PrP C is susceptible to conversion to the pathological PrP-scrapie form, and includes the binding sites for β1-integrin and amyloid-β, molecules implicated in several ocular disorders. Considering the species and tissue-specific cleavage of PrP C, our data suggest re-evaluation of prion infectivity and other ocular disorders of the human eye conducted in mouse models. Highlights: The prion protein (PrP C ) is mainly β-cleaved in the human ocular tissue. This contrasts with mainly α-cleaved PrP C in the human brain. β-Cleaved PrP C is relatively more susceptible to prion infectivity. This raises concerns of acquiring prion infection via the ocular route. PrP C in most animals is α-cleaved, requiring re-evaluation of infectivity studies.